Online Learning Innovation and Student Character Shift at UNZAH and UNUJA Probolinggo - Mamluatun Ni’mah; Edi Kurniawan Farid; Mohamad Ahyar Ma’arif; Muwahidah Nur Hasanah; Faisal Mahmoud Adam Ibrahim (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2023)
The shift in the learning system from face-to-face to online learning during the Covid-19 pandemic greatly impacted the shift in student character. Therefore, online learning innovations that are implemented must still lead to building character that is in line with educational goals. This study aims to explain the shifting in student character and online learning innovations during the Covid-19 pandemic at Zainul Hasan Genggong Islamic University (UNZAH) and Nurul Jadid University (UNUJA). This descriptive qualitative research uses observation, interviews, and documentation in data collection. The data were analyzed phenomenologically in descriptive narratives. The results are, First, there are various innovations at UNZAH in implementing online learning comprising policy, planning, implementation, and learning evaluation. This has resulted in shifts in the character of UNZAH students. However, the shift in student character leads to the building of the character of Pesantren Zainul Hasan Genggong, known as the term SANTRI and the 9 basic values of the santri. The shift in the character of UNZAH students are courtesy, honesty, trustworthiness, discipline, responsibility, love of knowledge and worship, and honor for teachers and parents. Second, innovation in implementing online learning at UNUJA starts with policies for implementing online learning and hybrid learning, planning, implementation, and evaluation. This has resulted in shifts in the character of UNUJA students. However, the shift in character leads to the trilogy character building and Panca Kesadaran of Pesantren Nurul Jadid. the shift in the character of UNUJA students are decent morals, inspirational-participative, disciplined, independence, and simplicity.